2020
DOI: 10.3390/pharmaceutics12080778
|View full text |Cite
|
Sign up to set email alerts
|

Combination Delivery of Alpha-Tocopheryl Succinate and Curcumin Using a GSH-Sensitive Micelle (PAH-SS-PLGA) to Treat Pancreatic Cancer

Abstract: Pancreatic cancer is one of the highest causes of mortality throughout the world; thus, it requires an effective treatment strategy. Some chemotherapeutic agents used in the clinics or under clinical trials are hydrophobic and have poor aqueous solubility; consequently, they also have minimal systemic bioavailability. Nanoparticle-based drug delivery tactics have the potential for overcoming these limitations and enhancing their therapeutic efficacy. Herein, a glutathione (GSH)-sensitive micelle (PAH-SS-PLGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In comparison to free drugs, nanoformulated drugs show different anticancer activity in the in vitro experiments which may be due to the drug release mechanism or their direct interaction with the cell of interest [ 39 ]. Hence, to study the in vitro cytotoxicity effect of the AUY922-loaded micelle, free AUY922, PLGA-Cys, and HA-SS-PLGA in the cellular proliferation of cancer cells, cell viability was evaluated by the MTT assay using brain cancer cells (i.e., U87, P5, and P5-TMZ-R).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to free drugs, nanoformulated drugs show different anticancer activity in the in vitro experiments which may be due to the drug release mechanism or their direct interaction with the cell of interest [ 39 ]. Hence, to study the in vitro cytotoxicity effect of the AUY922-loaded micelle, free AUY922, PLGA-Cys, and HA-SS-PLGA in the cellular proliferation of cancer cells, cell viability was evaluated by the MTT assay using brain cancer cells (i.e., U87, P5, and P5-TMZ-R).…”
Section: Resultsmentioning
confidence: 99%
“…The GSH-sensitive hyaluronic acid derivative (HA-SS-PLGA) was synthesized using two separate reaction steps, as shown in Scheme 1 . First, the carboxyl group of PLGA was activated with EDC/NHS and then one of the amine groups of cystamine reacted with the activated carboxyl group of PLGA to form PLGA-Cys (detailed synthesis protocols were mentioned in our previous paper) [ 39 ]. In the second reaction step, the carboxyl group of HA was activated in the presence of EDC/NHS and conjugated with the PLGA-Cys to form HA-SS-PLGA copolymer.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated CI values were observed to be less than one, which indicates a stronger synergistic effect for the nanoformulated drugs (PAH-SS-PLGA-TOS-curcumin) on cellular proliferation. Thus, it can be concluded that the selected drugs in combination can pave the way for enhancing the therapeutic efficacy and act as a treatment option for pancreatic cancer (Debele et al, 2020 ).…”
Section: Combination Based Onconanotherapeuticsmentioning
confidence: 99%
“…Taken together, nanotechnology can clearly help to offset resistance either by correcting physiological alterations in tumours, or by exploiting them for on-demand drug release. Aside from pH and oxygen status, interest in other tumour features, such as elevated glutathione levels, has also produced encouraging results that are worthy of further investigation [ 223 , 224 , 225 , 226 , 227 ].…”
Section: Addressing Therapy Resistance In Paca Using Nanoparticle-based Platformsmentioning
confidence: 99%